The Crucial in Acquiring Waqf in Holly Qur’an Surah Al-‘Alaq 1-5 (Study of Tafseer Ibn Katsir and Al-Misbah) - Heru Saiful Anwar; Muhammad Bahrul Hasan (Educan : Jurnal Pendidikan Islam, 2018)
It is the fact that the Qur’an is the word of God, which wa delivered by the Prophet Muhammad, as a guide for humans in organizing their lives, the world and the hereafter. The purpose of this day is to: 1) reveal the importance of learning Waqf in Tafseer Ibn Katsir in surah Al-‘Alaq verses 1-5. In the interpretation of surah Al-‘Alaq verses 1-5 during the interpretation of Ibn Katsir and Al-Misbah. According to Ibn Katsir by carrying out the learning process humans, will obtain knowledge. It is necessary to discuss, to develop knowledge and to conduct investigations on all that is not known and know. By ‘ilm (knowledge), Allah elevate human degrees, 2) According to Tafseer Al Misbah, Islam instructs humans to learn from written and oral texts and everything that comes from Allah and humans that was equipped with the intention of devotion to God. 3) The similiarity: Tafseer Ibn Katsir and Al-Misbah agreed that reading is important in human life. This is the key to science. Learning is an obligation for humans because after the learning process comes from new science unless he knows, and science raises God. The difference point was: Ibn Katsir explained the verses of Qur’an is in brief. Besides, Ibn Katsir stated the history of ayat with the essential of knowledge in the human life. Tafseer Al Misbah the verses of Qur’an separately. Moreover, he enclosed the statement of other mufasirin.